2023
DOI: 10.1177/0306624x221144298
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence During the Corona Pandemic: A Comparison of Pre-Pandemic and Pandemic Incidents of Domestic Violence in the Netherlands

Abstract: There is a widespread fear that the measures as a consequence of the worldwide corona pandemic have led to a significant increase in domestic violence and child abuse. The current study uses criminal files from all incidents of domestic violence that were reported to the police in a relatively large city in the Netherlands during 3.5 months before the pandemic and the first 3.5 months from the start of the nationwide shutdown, to compare the characteristics of the incident, the suspect and victim, how the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…(Kartadinata et al, 2015) Peace in domestic life is a bottom-up peacebuilding intervention effort (Brück & Ferguson, 2020;Cocodia, 2023;García-Sánchez et al, 2022). However, various problems that occur in households such as domestic violence (Alimi & Nurwati, 2021;Ariyanti & Ardhana, 2020;Demir & Park, 2022;Haque et al, 2022;Karim & Swahnberg, 2021;Lee, 2019;Van Koppen et al, 2023), infidelity (Irvine & Peluso, 2022;Luo & Yu, 2022;Pramudito & Minza, 2021), and the high divorce rate (Hidayati, 2021;Manna et al, 2021;Puspitawati et al, 2021;Zahl-Olsen, 2023) indicate that marriages are vulnerable to issues of disharmony.…”
Section: Introductionmentioning
confidence: 99%
“…(Kartadinata et al, 2015) Peace in domestic life is a bottom-up peacebuilding intervention effort (Brück & Ferguson, 2020;Cocodia, 2023;García-Sánchez et al, 2022). However, various problems that occur in households such as domestic violence (Alimi & Nurwati, 2021;Ariyanti & Ardhana, 2020;Demir & Park, 2022;Haque et al, 2022;Karim & Swahnberg, 2021;Lee, 2019;Van Koppen et al, 2023), infidelity (Irvine & Peluso, 2022;Luo & Yu, 2022;Pramudito & Minza, 2021), and the high divorce rate (Hidayati, 2021;Manna et al, 2021;Puspitawati et al, 2021;Zahl-Olsen, 2023) indicate that marriages are vulnerable to issues of disharmony.…”
Section: Introductionmentioning
confidence: 99%
“… 10. Van Koppen et al (2023) analysed police records of cases of domestic violence that were reported in a large city in the Netherlands during 3.5 months before the pandemic and the first 3.5 months of the lockdown. Their results show that reported cases of domestic violence did not increase.…”
mentioning
confidence: 99%